Teacher Educators’ Perceptions of Critical Incidents in Teaching Practice: The Case of Novice EFL Teachers - Estaji, Masoomeh; Ahmadi Fatalaki , Javad (East European Journal of Psycholinguistics, 2022)
Teachers experience various challenges and conditions in their profession, and they may require to make appropriate decisions and take action based on the analysis of the situation. The present study attempted to identify the critical incidents that occur in teaching practices for the novice teachers from the teacher educators’ standpoint. Moreover, they were asked to offer some solutions for these critical incidents. To do so, eight teacher educators at a teacher education university in Iran were asked to be involved in a semi-structured interview to openly express their views. Content and thematic analyses were carried out on the transcript of the interviews. Based on the findings, teacher educators referred to nine major incidents in the teachers’ pedagogical practices and offered six solutions. The major incidents included time management, the students’ ineffective cooperation, odd behavior, demotivation, dissatisfaction, lack of empathy and sympathy, the teacher’s content knowledge, and the required type of feedback. The solutions provided by the teacher educators were familiarizing the pre-service teachers with the critical incidents, management strategies, use of classroom observation, running workshops, reflective practice, and emotional intelligence development. The research results help novice and pre-service teachers to identify the critical incidents, reflect upon them, and be prepared to react appropriately. Moreover, the results confirm the necessity of a course, emphasizing both the critical incidents and the probable solutions.